The Role of Exosomes in the Progression and Therapeutic Resistance of Hematological Malignancies - Wang, Haobing; You, Yong; Zhu, Xiaojian (Frontiers in Oncology, 2022)
Exosomes are membrane limited structures which derive from cell membranes and cytoplasm. When released into extracellular space, they circulate through the extracellular fluid, including the peripheral blood and tissue fluid. Exosomes surface molecules mediate their targeting to specific recipient cells and deliver their contents to recipient cells by receptor-ligand interaction and/or phagocytosis and/or endocytosis or direct fusion with cell membrane. Like hormones, exosomes mediate intercommunication between cells, and because the functional complexity of their cargos, including nucleic acids (DNAs, mRNAs, non-coding RNAs), proteins (transcription factors, enzymes, etc.), and lipids which have biological activity, exosomes are extensively involved in physiological and pathological processes, such as angiogenesis, matrix reprogramming, coagulation, tumor progression. In recent years, researcher have found that exosomes from malignant tumors can mediate information exchange between tumor cells or between tumor cells and non-tumor cells, thereby promoting tumor survival, progression, and resistance to therapy. In this review, we discuss the pro-tumor and anti-therapeutic effects of exosomes in hematological malignancies, hoping to contribute to the early conquest of hematological malignancy.